Mesoionic Carbene Cobalt Complexes as Multipurpose Catalyst Precursors for Hydrosilylation and Dihydropyrimidinone Synthesis. Issue 12 (2nd November 2021) - Bertini, Simone; Albrecht, Martin
Abstract: Metalation of CH2 OH‐substituted triazolium salts with CoCl2 under basic conditions affords C, O ‐bidentate chelating carbene Co(III) complexes (3a, 3b ), while analogous phenyl‐substituted triazolium salts produce monodentate carbene Co(II) complexes (3c, 3d ). The distinct substituent‐induced properties of the metal centers were demonstrated by electrochemical measurements and catalytic activities in two specific processes. The complexes showed appreciable activity in the reduction of C=O bonds through hydrosilylation, with methoxybenzene‐functionalized triazolylidene Co(III) complex 3a achieving a high selectivity towards aldehydes vs . ketones with turnover frequencies (TOFs) up to 200 h −1 . The C, O ‐chelate systems were also active catalysts in the Biginelli process, a one‐step three‐component reaction for efficient dihydropyrimidinone synthesis. Optimization of reaction conditions provides high activity with complex 3a, reaching TOFs of 800 h −1, the highest activity known for cobalt NHC complexes to date. Abstract :